THE EFFECT OF METAL IONS, OXALATE AND AMINOACIDS ON THE ACTITIVITY OF PYRUVATE KINASE FROM CURIMBATÁ (Prochilodus lineatus) EPAXIAL MUSCLE - GILLI, M.R.M.S.; OCAMPOS, D.; PUGINE, S.M.P.; LAVANDEIRA, L.; CERQUEIRA CESAR, M.; ROSA, R.; BACILA, M. (Archives of Veterinary Science, 2000)
Foi realizada pesquisa sobre o efeito de ions divalentes, do oxalato e de aminoácidos sobre a atividade da piruvatoquinase (PK) de purificada do músculo epaxial do peixe tropical, curimbatá (Prochilodus lineatus). Essa preparação e PK é ativada por Mg e Mn sendo sensível à ação de Cu , Co , Ni e Zn . Ni e Zn inibem a atividade da enzima em cerca de 70% e 80% respectivamente. A atividade da presente preparação de PK é inibida em cerca de 85% por oxalato na concentração de 2 mM. A piruvatoquinase do músculo epaxial do curimbatá mostra diversas características de isoenzima M2 mas não é inibida pela L-alanina. Abstract A research has been carried out on the effect of divalent ions, oxalate and aminoacids on the activity of pyruvatekinase (PK) purified from the epaxial muscle of the tropical fish curimbatá (Prochilodus lineatus). This preparation of PK is activated by Mg2+and Mn2+ being sensitive to Cu2+, Co2+, Ni2+ and Zn2+. Ni2+ and Zn2+ inhibit PK activity in about 70% and 90%, respectively. The activity of this PK preparation is inhibited in about 85% by 2mM oxalate. In regard to aminoacids, PK from curimbatas epaxial muscle displays several characteristics of M2 isoenzymes, but is not inhibited by L-alanine.